The photophysical and photochemical properties of new unmetallated and metallated phthalocyanines bearing four 5-chloroquinolin-8-yloxy substituents on peripheral sites - Nas, Asiye; Demirbas, Umit; Piskin, Mehmet; Durmuş, Mahmut; Kantekin, Halit (Elsevier Science Bv, 2014)
The synthesis and characterization of novel peripherally tetrakis-(5-chloroquinolin-8-yloxy) substituted metal-free (4), zinc(II) (5), lead(II) (6), cobalt(II) (7), copper(II) (8) and nickel(II) (9) phthalocyanines are described for the first time in this study. The spectroscopic, photophysical (fluorescence quantum yields and lifetimes) and photochemical properties (singlet oxygen production and photodegradation under light irradiation) of metal-free (4), zinc(II) (5) and lead(II) (6) phthalocyanines are investigated in N,N-dimetilformamid (DMF). The newly synthesized cobalt(II) (7), copper(II) (8) and nickel(II) (9) phthalocyanine compounds were not evaluated for this purpose due to open shell nature of these central metals in the phthalocyanine cavity. The influence of various the nature of the central metal ion (zinc, lead or without metal) on these properties has also been investigated and compared. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Phthalocyanine; Photophysics; Photochemistry; Fluorescence; Singlet oxygen; Photodegradation